Optimizing chemical and mechanical stability of catalytic nanofiber web for development of efficient detoxification cloths against CWAs. (1st February 2021) - Seo, Eunbyeol; Kim, Hyejin; Bae, Kihyeon; Jung, Heesoo; Jung, Hyunsook; Lee, Kyung Jin
Abstract: N–Cl functional groups have been widely utilized for antimicrobial and detoxification purpose. However, along with the high reactivity of N–Cl moiety, long term stability of N–Cl moiety under ambient condition is of special interest for final applications. Diverse organic moieties have been developed to enhance N–Cl stability, and hydantoin N–Cl groups are generally accepted as a promising candidate. Here, N–Cl functionalized electrospun nanofibers are prepared via surface functionalization method for fabrication of catalytic nanofiber mat against chemical warfare agent. Thermoplastic polyurethane (TPU) containing abundant pandent azide moiety is firstly synthesized, and nanofiber web is prepared via electrospinning. Hydantoin functional groups that are well-known moiety to stabilize N–Cl functional groups are introduced via surface click reaction. The storage stability of N–Cl groups from surface reaction is superior than that of bulk reaction with maintaining their catalytic activity for decomposition of chemical warfare agents. In order to increase mechanical properties of nanofiber web, amount of hydantoin groups on surfaces has been controlled by blending of normal TPU with azide TPU, and blended nanofiber web maintains their inherent flexibility after hydantoin functionalization and N-chlorination. Optimized blending conditions to achieve both of high N–Cl stability and enhanced catalytic activity have been traced. Surface rich N–Cl groups show better stability with maintaining their inherent catalytic activities. Graphical abstract: Nanofiber mat having large amount of N–Cl functional groups for catalytic applications can be prepared via electrospinning of azide TPU, click reaction and N–Cl treatment. Surface localized hydantoin N–Cl functional groups can be prepared by surface click reaction on azide TPU nanofibers. These surface localized N–Cl groups not only show high enough catalytic efficiency for simulant of chemical warfare agent, but also have enhanced long-term stability compared to bulk N–Cl groups. Image 1 Highlights: N–Cl functionalized electrospun nanofibers are prepared via surface functionalization method. The storage stability of N–Cl groups from surface reaction is superior than that of bulk reaction. Amount of hydantoin groups on surfaces has been controlled by blending method. Over 90% of detoxification yield can be achieved against 2-CEES.